Youth as Actors of Change? The Cases of Morocco and Tunisia. Issue 2 (3rd April 2018) - Paciello, Maria Cristina; Pioppi, Daniela
Abstract: In the last decades, 'youth' has increasingly become a fashionable category in academic and development literature and a key development (or security) priority. However, beyond its biological attributes, youth is a socially constructed category and also one that tends to be featured in times of drastic social change. As the history of the category shows in both Morocco and Tunisia, youth can represent the wished-for model of future citizenry and a symbol of renovation, or its 'not-yet-adult' status which still requires guidance and protection can be used as a justification for increased social control and repression of broader social mobilisation. Furthermore, when used as a homogeneous and undifferentiated category, the reference to youth can divert attention away from other social divides such as class in highly unequal societies.